Digital advances in modern pathology - Sandle, T.; Chesca, A.; Abdulina, G. (Fundamental and Experimental Biology, 2018)
This review has considered some of the developments that have taken place with and which are shaping digital pathology. Of the different technologies surveyed, digital imaging is the one that will be adopted at the fastest rate. Today software programs enable pathologists to create and read the digital «slides.» Unlike traditional histological samples, microscopic users are able to create digital images almost any tissue sample traditionally viewed under a microscope. The advantages offered by cloud computing also allow researchers to create accessible databases and to share images rapidly. In outlining current trends, the chapter has described many of the advantages that arise from digitalization. The process remains a developing arena, however and there remain barriers to adoption. Barriers to adoption include limiting technology, image quality, problems with scanning all materials (e.g., cytology slides), cost, digital slide storage, inability to handle high-throughput routine work, regulatory barriers, ergonomics, and pathologists’ reluctance. In time, many of these will be overcome as technology and education move on. Some possibilities of digital technology are facilitating personalized medicine where therapies are tailored to the individual and also empowering people to manage their own health through access to electronic health records. How quickly these come to pass remains to be seen; the key message is, however, that digital technology is transforming healthcare and the future delivery of pathology services in new and remarkable ways.